ANALYSIS OF ZERO RUPIAH DOWN PAYMENT HOUSE POLICY FORMULATION FOR LOW INCOME COMMUNITIES IN DKI JAKARTA - Harry Nenobais; Asnawi (Moestopo International Review on Social, Humanities, and Sciences, 2021)
This study describes the public policies of the DKI Jakarta Provincial Government on housing assistance for law-Income Communities. DKI Jakarta as the center of Government and economy attract people to come to the city. The scarcity and the high price of land in DKI Jakarta factors into the number of Low-Income Communities in the city who struggle to own housing/ property. The study aims to analyze the policy formulation of DKI Jakarta Provincial Government on the assistance in providing decent housing needs the policy formulation of the DKI Jakarta Provincial Government for assistance in providing decent housing needs for Low-Income Communities. The research uses descriptive qualitative methods by using primary and secondary data. Data and information are obtained through interviews with the actors involved in the process of policy formulation, surveys and taking photographs related to the Zero Rupiah Down Payment House and document that can support research. From the analysis, it is found in the formulation of the Zero Rupiah Down Payment House Program policy that there should be stronger legal basis and a set of wage margin for Low-Income Communities in DKI Jakarta as well as supervision in the implementation of the program so that it is targeted to the Low- Income community by paying attention to aspects of alignments to the community need.